Non-Disclosure Agreement in Its Application to Breach of Contract Lawsuits Referred to From Article 1320 of The Civil Code - Devina Septy Fathikhah; Sri Waljinah (Proceeding International Conference Restructuring and Transforming Law, 2026)
Indonesia, as a nation governed by law, as stipulated in the 1945 Constitution, makes law the fundamental regulatory framework for all aspects of life, including employment relationships. In its implementation, protecting trade secrets is crucial due to the increasing risk of leaking information of significant economic value. The legal instruments used are:Non-Disclosure Agreement (NDA), although until now there are no specific provisions in the law. This study aims to analyze whether the NDA is valid and legally binding in employment relations, referring to Article 1320 of the Civil Code. This study also examines the impact of violations of the agreement on breach of contract lawsuits, using a case study that occurred at PT Foom Lab Global. The method in this study uses a juridical-normative approach and focuses on the provisions of the law and analyzes the case that occurred. The legal materials include primary legal materials in the form of the Civil Code, Law 30/2000 concerning Trade Secrets, and court decisions, then secondary legal materials in the form of scientific readings. The study proves that the NDA is legally valid and binding if it is in line with the provisions of a valid agreement. In the case of PT Foom Lab Global against Sulfa Sopiani, the Defendant was proven to have committed a breach of contract in the form of violations of resignation procedures, violations of the non-competence clause, and potential violations of information confidentiality. The Defendant was sentenced to pay compensation of 800 million. This ruling states that NDAs can be legally enforced as long as they are drafted correctly and in a balanced manner. The study concludes that NDAs are an effective legal tool for protecting trade secrets, but their implementation must adhere to the principles of fairness and balance in employment relationships to avoid harming workers' rights.